2003
DOI: 10.1074/jbc.m300101200
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of the Phospholipase C-δ1 Pleckstrin Homology Domain Located at the Lipid Bilayer Surface

Abstract: Despite the importance of signal transduction pathways at membrane surfaces, there have been few means of investigating their molecular mechanisms based on the structural information of membrane-bound proteins. We applied solid state NMR as a novel method to obtain structural information about the phospholipase C-␦1 (PLC-␦1) pleckstrin homology (PH) domain at the lipid bilayer surface. NMR spectra of the alanine residues in the vicinity of the ␤5/␤6 loop in the PH domain revealed changes in local conformations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 26 publications
4
41
0
Order By: Relevance
“…So far, the mechanism through which PHβ2 binds to membranes is unknown in contrast to PHδ 1 whose membrane interactions have been clearly identified [4,50]. A structural model of PHβ 2 and subsequent simulation of its insertion into an electrically neutral membrane allows us to propose a dominant membrane orientation where the 71-88 region resides on the membrane surface (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…So far, the mechanism through which PHβ2 binds to membranes is unknown in contrast to PHδ 1 whose membrane interactions have been clearly identified [4,50]. A structural model of PHβ 2 and subsequent simulation of its insertion into an electrically neutral membrane allows us to propose a dominant membrane orientation where the 71-88 region resides on the membrane surface (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…This activation had been previously missed since the activator, PI(4,5)P 2 , was the same as the substrate. It should be noted that the PH-δ1 is not a rigid lipid-binding domain since a slight conformational change, involving a small amphipathic helix of β5/β6 loop occurs upon binding to PI(4,5)P 2 and this change is regulated by the phosphatidylserine content in membranes [80,81]. Roberts and collaborators also suggest that the PH domain may have an allosteric role in PLC-δ1 activity [20].…”
Section: Role Of the Ph Domain In Plc-δ1 And Plc-β2 Activationmentioning
confidence: 99%
“…Comparing a model structure of PH-β2 with the known structure of PH-δ1 suggests that the β5/β6 loop, which is longer than in PH-δ1, (Figure 3) could act as a regulatory domain for activation by Gβγ [41]. A peptide corresponding to this loop (PHβ [71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88] ) activates the enzyme, and this activation is competitive with Gβγ activation. The structure of PLC-β2 reveals that the β5/β6 loop does not belong to the surface that is tightly packed with the EF-hands and the catalytic regions, or to the hydrophobic ridge interacting with Rac2.…”
Section: Role Of the Ph Domain In Plc-δ1 And Plc-β2 Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is largely because of the presence of a large number of cationic residues and the apparent lack of hydrophobic residues on their membrane-binding surfaces (32,51). However, recent studies have indicated that the PH domain of phospholipase C (PLC) ␦1 significantly penetrates the membrane (52,53).…”
mentioning
confidence: 97%